Obstacles and Challenges in Implementing Flogging Law for Khalwat Offenders - Dari, Wulan; Yazid, Imam (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Aceh Province holds a special status in Indonesia, allowing the formal implementation of Islamic sharia through Qanun, including sanctions for khalwat (seclusion between non-mahram individuals). Specific Background: Qanun Jinayat No. 6/2014 explicitly categorizes khalwat as a jarimah punishable by flogging, but its enforcement in Aceh Tenggara remains inconsistent and contested. Knowledge Gap: Previous studies largely examined normative or localized aspects, leaving insufficient exploration of the multidimensional obstacles—structural, cultural, juridical, and procedural—that undermine the law’s effectiveness. Aims: This study seeks to identify, analyze, and evaluate the obstacles and challenges faced in enforcing flogging sanctions against khalwat perpetrators in Aceh Tenggara, and to formulate strategic solutions. Results: Findings reveal that weak institutional capacity, limited training, overlapping legal norms, community resistance, and social pressures on law enforcement significantly hinder consistent and fair implementation. Novelty: Unlike earlier works, this study provides a comprehensive analysis that integrates legal theory with empirical insights, offering a holistic view of enforcement challenges. Implications: Strengthening inter-agency coordination, enhancing officer capacity, and promoting community legal awareness are essential to ensure that sharia enforcement in Aceh is more effective, just, and contextually responsive to societal dynamics. Highlights: Structural, cultural, and juridical barriers weaken effective implementation. Social resistance and weak institutional capacity hinder law enforcement. Strengthening officer training and inter-agency coordination is crucial. Keywords: Flogging Law, Khalwat, Qanun Jinayat, Legal Enforcement